KARAKTER GENETIK DAN STRUKTUR POPULASI IKAN NAPOLEON, Ceilinus undulatus DI PERAIRAN INDONESIA - Moria, Sari Budi; Haryanti, Haryanti; Permana, Gusti Ngurah; Slamet, Bejo (Jurnal Riset Akuakultur, 2006)
KARAKTER GENETIK DAN STRUKTUR POPULASI IKAN NAPOLEON, Ceilinus undulatus DI PERAIRAN INDONESIA